Photon indistinguishability measurements under pulsed and continuous excitation - Ross C. Schofield; Chloe Clear; Rowan A. Hoggarth; Kyle D. Major; Dara P. S. McCutcheon; Alex S. Clark (Physical Review Research, 2022)
The indistinguishability of successively generated photons from a single quantum emitter is most commonly measured using two-photon interference at a beam splitter. Whilst for sources excited in the pulsed regime the measured bunching of photons reflects the full wave-packet indistinguishability of the emitted photons, for continuous wave (cw) excitation, the inevitable dependence on detector timing resolution and driving strength obscures the underlying photon interference process. Here we derive a method to extract full photon wave-packet indistinguishability from cw measurements by considering the relevant correlation functions. The equivalence of both methods is experimentally verified through a comparison of cw and pulsed excitation measurements on an archetypal source of photons, a single molecule.